POET-POMANTICIST STRUGGLING AGAINST EVIL: TARAS SHEVCHENKO AND WRITERS - Yakubovs’ka-Kravchyk, K. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines poetic works of Taras Shevchenko and Polish writers. Their creation is analysed from the point of view of romantic philosophy, according to which all kinds of art must serve first and foremost truth and under its influence inner life of both each person and of whole nations.